Kyrgyz Republic Public Expenditure Review : Better Spending for Building Human Capital - World Bank (World Bank, Washington, DC, 2021)
The Kyrgyz Republic economy has been hit hard by the Coronavirus disease of 2019 (COVID-19) pandemic, putting at risk the development progress achieved in recent years. The COVID-19 pandemic has added substantial pressures on the country’s fiscal space for investing in human capital. The pandemic has eroded the Kyrgyz Republic’s recent gain in human capital development. Education and health are critical factors for improving human capital and sustaining inclusive economic growth and development. The Kyrgyz Republic has continued prioritizing education and social protection as its development priority. This report, phase 2 of the programmatic public expenditure review (PER2), aims to assist the government of the Kyrgyz Republic in identifying key constraints to efficient and effective public spending and policy options for improvements in three areas: education, health, and pensions, which have become more pressing post-COVID-19. Ensuring effective and sustainable pension system may help to safeguard human capital. Hence, ensuring adequacy, effective, and efficient spending in education, health, and pensions are critical to close Kyrgyz’s human capital gaps. To this end, PER1 identified critical areas to increase fiscal space for development priorities including investing in human capital including curtailing the growth of public wages while reducing tax expenditures and the large energy subsidies and quasi-fiscal deficits.